Metabolomics combined with chemometric analysis to identify α-glucosidase inhibitors in Phaleria macrocarpa fruit extracts and its molecular docking simulation - Easmin, Sabina; Sarker, Zaidul Islam; Khatib, Alfi; Ferdosh, Sahena; Jaffri, Juliana; Uddin, ABM Helal; Murugesu, Suganya; Balan, Tavamani; Perumal, Vikneswari (Elsevier, 2024)
Phaleria macrocarpa is a medicinal plant widely available in Malaysia. The plant parts have been traditionally used as an antidiabetic remedy. This study aimed to identify the putative inhibitors of the α-glucosidase enzyme from P. macrocarpa using a gas chromatography-mass spectrometry (GC–MS)-based metabolomics approach and further subjected them to in silico molecular docking analysis to elucidate the possible mechanism of action. This study assessed the inhibitory potential of P. macrocarpa fruit extracts (aqueous, 20 %, 40 %, 60 %, 80 %, and 100 % ethanol) against the α-glucosidase enzyme using GC–MS and chemometric analysis. Orthogonal partial least squares (OPLS) combined with GC–MS analysis were applied to correlate the inhibition of enzyme activity to the metabolites profile of P. macrocarpa. All the potential inhibitors identified were further docked to the yeast (Saccharomyces cerevisiae) protein crystal structure (PDB3A4A). The generated score scatter plot of OPLS showed a recognizable separation of all the extracts into six different clusters. GC–MS, incorporated with multivariate data analysis techniques, was used to identify significant chemical markers. Methyl α-D-glucopyranoside, squalene, palmitic acid, myo-inositol and isoquinoline metabolites were identified as putative inhibitors against α-glucosidase activity from P. macrocarpa. In conclusion, the GC–MS-based metabolomics approach identified potential chemical markers of P. macrocarpa that could be utilized in the development of herbal based medicine. © 2024 SAAB